Recurrent pericarditis in an adolescent with Crohn's colitis - Bibhuti B Das; Morgan Dodson; Angel Guzman (Wolters Kluwer Medknow Publications, 2020)
Extraintestinal manifestations are common complications of inflammatory bowel disease (IBD), whereas the recurrent pericarditis during remission of Crohn's disease is rarely reported. Chest pain developed in a 13-year-old adolescent male who had a history of Crohn's colitis since 9 years of age and was in remission for 4 years after treatment with infliximab, adalimumab, and vedolizumab. Physicians should be aware of the pericardial involvement in patients with a history of IBD. The literature on pericardial involvement in Crohn's disease is reviewed with emphasis on the management of recurrent pericardial effusion in the pediatric age group.